Correlation of Polypharmacy and Comorbidity with NIHSS Status in Ischemic Stroke Patient - Wardhani, Firdha A. (Universitas Padjadjaran, Indonesia, 2023)
Drug-related problems are a common problem among stroke patients due to comorbidities resulting from the complex management of stroke treatment leading to polypharmacy management. Studies show that 90% of stroke patients have drug-related problems (DRPs). However, there is limited information on the impact of comorbidities as risk factors for DRP prevalence and unfavorable prognosis in patients with ischemic stroke. This study aimed to determine the risk factors for DRP and clinical outcomes as modifiable comorbidities in ischemic stroke patients admitted to a tertiary hospital between January 2020 and October 2021 were indeed significant influences. The study was conducted retrospectively using a cross-sectional analysis of patient’s medical records. The study found no significant association between the presence of comorbidities and polypharmacy in patients with the incidence of DRP, although we found that the DRPs occurrence was found more in a patient with comorbidities and polypharmacy. Diabetes mellitus was found to have a significant association with no improvement in NIHSS scores in ischemic stroke patients. We found that diabetes mellitus patient had an increased risk of non-improvement NIHSS score 2,987 times compared to patients without diabetes mellitus. The second increased risk was the presence of comorbid hypertension (OR 1.352), the third was the occurrence of polypharmacy (OR 1,175), and the fourth was dyslipidemia (OR 1.138).